Tipificação do delito de infidelidade patrimonial no ordenamento jurídico brasileiro - Maciel, Hellen de Macêdo (2023)
This master's thesis proposes to analyze the need to typify the crime of patrimonial infidelity in the Brazilian legal system, given the existence of gaps in punishment. This is a theme that has been highlighted in recent years, due to the crime of patrimonial infidelity being considered as the economic crime par excellence of our time. Thus, we sought, firstly, to investigate the reasons why property crimes, with a focus on economic criminality, face resistance to their typification in the various legal systems, analyzing the criminal selectivity specifically regarding property crimes. In this sense, it was concluded that the typical prediction of the crime of patrimonial infidelity also finds specific roots in globalization and in the evolution of modern relations, linking its prediction to a movement for the conservation of ethics and integrity in corporate structures. Although its legal provision in other legal systems is not recent, it still encounters certain obstacles regarding the exact determination of its typical elements, demanding a careful study of its unfairness, indeed complex, as well as the subjective element and the legal relationship of trust that underpins the criminal type. The work seeks to break down, as much as possible, the most important aspects of the legal dogmatics of the offense in question, especially with regard to objective imputation and the business judgment rule. Still, it proves the existence of a punishment gap for concrete facts defined as patrimonial infidelity that are commonly captured and absorbed by existing criminal types, being applied by the judges, through an extensive interpretation and inevitably leading to a violation of the principle of legality and the realization of analogies against the defendant